Factors influencing customer satisfaction towards the light rail transit (LRT) in Kuala Lumpur - Stephen, Theresa; Musa, Musalliana; Kamarudin, Farasyila; Idris, Anisah; Wok, Saodah (2018)
This article aims to provide a case study of the light rail transit (LRT) in the Klang Valley, Malaysia from the users’ perspective on the usage of the LRT. It explores factors that influence customer satisfaction in using the LRT such as safety, convenience, accessibility, affordability and meeting customer expectation. The study uses a quantitative research design which emphasises objective measurements and the statistical analysis of data collected through a survey questionnaire. It uses a framework of the five dimensions of safety, convenience, accessibility, affordability and expectations of their satisfaction using the Theory of Planned Behaviour and the Social Exchange Theory. It is discovered that the preferred factors influencing the usage of the LRT are safety, convenience and affordability. Accessibility and expectations influence the satisfaction of users at a minimal level. When the customer is satisfied with the services or products, the customer will be committed to keep on using the preferred products or services consistently in the future. The study recommends that stakeholders improve the quality of services to automatically generate revenue in the future as the underlying implication is that customers have a strong impact on company profits because they buy more when services are satisfactory. It is hoped this study will raise government awareness of the potential improvement of LRT services to increase the use of the public transportation system in Malaysia. This is in line with the efforts to reduce expenditure on traffic and parking for locals and to assist Prasarana Malaysia Berhad to identify the key factors in maintaining and improving the quality of their service.